AB0461 ANCA-ASSOCIATED VASCULITIS: CLINICAL FEATURES, RELAPSE, ORGAN DAMAGE AND SURVIVAL IN 197 PATIENTS. (2nd June 2020) - Bektas, M.; Ince, B.; Agargun, B. F.; Guzey, D. Y.; Yalçinkaya, Y.; Artim-Esen, B.; Gül, A.; Ocal, M. L.; Inanc, M.
Abstract : Background: ANCA-associated vasculitis (AAV) is a multisystemic autoimmune disease with high mortality and morbidity. Objectives: We aimed to present the long-term follow-up results of our cohort. Methods: Data of patients who fulfilled Chapell Hill Consensus Criteria and followed up at least 6 months between 1999-2019 were analyzed. A standard form including vasculitis damage index (VDI) was used. Multivariable analysis was performed by using logistic regression. Results: Long-term data was available for 197 patients (%53.8 female) from 208 patient records. Mean age at diagnosis was 49.4 years and mean follow-up was 80.7 months. Granulomatosis with polyangiitis (GPA); microscopic polyangiitis (MPA), eosinophilic GPA (EGPA) were 117 (64.5%), 52 (26.4%), 17 (8.6%), respectively. Relapses are observed in 31.6% of patients. Disease relapses were higher in GPA compared to MPA and EGPA (p = 0.014). Relapse rate was higher in patients with s.aureus carriage (p = 0.037). Cyclophosphamide (CYC) (76.6%) was most commonly used drug for induction, whereas azathioprine (57.3%) was used mostly in maintenance. In multivariate analysis relapse was found to be associated with maintenance treatment with rituximab (p <0.001), venous thrombosis (p=0.046) and serious infection (p<0.004). There was no significant association between relapse and mortality. Five-year survival rates were 98.5% for GPA, 88.5% for MPA and 100% for EGPA. Nineteen patients died during follow-up (9.6%). In univariate analysis mortality were high in MPA patients. Low hemoglobin and increased creatinine at baseline, subglottic stenosis, polyneuropathy, and cerebrovascular events (CVE) were associated with increased mortality. In multivariable analysis, mortality was associated with CVE (p=0.047) and anti-MPO positivity (p=0.014). Malignancy was developed in 9 patients (M / F: 7/2; two lung, three bladder, one cervix, one thyroid papillary, one kidney and one of unknown primary). There was no association between malignancy and cumulative dose of CYC. Venous thromboembolism was developed in 12 (6 %) and avascular necrosis (AVN) was detected in 30 patients (15.4%). Most (88.7%) patients developed damage during follow-up. Mean VDI score was 2.6 and VDI score was found to be higher in GPA (p= 0.035). There was no association between VDI score and mortality. Conclusion: In our AAV cohort, GPA was most frequent. Although survival was improved, permanent organ damage was detected in the majority of patients. Relapse and organ damage were found to be increased in patients with GPA. Relapses are frequent and maintenance with rituximab could not prevent relapses. Also relapses were associated with venous thrombosis and severe infections. Patients should be screened for malignancies especially of the genitourinary tract. Disclosure of Interests: None declared